Negative control of BAK1 by protein phosphatase 2A during plant innate immunity. (1st August 2014) - Segonzac, Cécile; Macho, Alberto P; Sanmartín, Maite; Ntoukakis, Vardis; Sánchez‐Serrano, José Juan; Zipfel, Cyril
Abstract Recognition of pathogen‐associated molecular patterns (PAMPs) by surface‐localized pattern‐recognition receptors (PRRs) activates plant innate immunity, mainly through activation of numerous protein kinases. Appropriate induction of immune responses must be tightly regulated, as many of the kinases involved have an intrinsic high activity and are also regulated by other external and endogenous stimuli. Previous evidences suggest that PAMP‐triggered immunity (PTI) is under constant negative regulation by protein phosphatases but the underlying molecular mechanisms remain unknown. Here, we show that protein Ser/Thr phosphatase type 2A (PP2A) controls the activation of PRR complexes by modulating the phosphostatus of the co‐receptor and positive regulator BAK1. A potential PP2A holoenzyme composed of the subunits A1, C4, and B'η/ζ inhibits immune responses triggered by several PAMPs and anti‐bacterial immunity. PP2A constitutively associates with BAK1 in planta. Impairment in this PP2A‐based regulation leads to increased steady‐state BAK1 phosphorylation, which can poise enhanced immune responses. This work identifies PP2A as an important negative regulator of plant innate immunity that controls BAK1 activation in surface‐localized immune receptor complexes.